Квантовая частица под воздействием сил типа "белого шума" - Гихман, И.И. (Український математичний журнал, 1993)
We obtain the Schrödinger equation for the wave function of a particle interacting with the external field having a potential containing a component of the “white noise” type and the Kolmogorov equations for the distribution of a wave function.